Education and development: outcomes for equality and governance in Africa. - Ndulo, B.M Muna, B..Ndulo; T.N'Dri.A.L Assies-Lumumba.T.N'Dri (USA: Palgrave macmillan., 2020)
This edited volume addresses a critical aspect of development in Africa: the intersection between education and governance. Using case studies and experiences from different parts of the continent, this book assesses how the potential for human resources, in terms of education, can be leveraged in the development process to achieve equity, inclusive development and governance outcomes in Africa. This book builds on the "resource curse" to focus on human resources as an alternative paradigm to sustainable development in Africa. At a time when concerns over access to quality education is an important issue among policy makers and international development agents, this timely project calls attention to one of the most critical aspects of development in Africa.
Includes bibliography references and index